FEASIBILITY ANALYSIS OF MULTI-BUSINESS FORESTRY IN SOCIAL FORESTRY IN FOREST AREAS WITH SPECIAL MANAGEMENT (KHDPK) - Widiyanto, Ary; Nurrochmat, Dodik Ridho; Trison, Soni; Subarudi (Association of Indonesian Forestry and Environment Researchers and Technicians, 2026)
The concept of multi-business forestry (Mb-F) aims to increase the economic benefits of forests, which have thus far made little contribution, without ignoring their ecological functions. The opportunity to develop multi-business forestry in social forestry (SF) activities within the Forest Area with Special Management (Kawasan Hutan Dengan Pengelolaan Khusus/KHDPK) is huge. With one area management permit, many business activities can be carried out. This study aims to determine the feasibility of multi-business forestry using screening method for social acceptance (community preference), financial feasibility (NPV, B/C Ratio, and IRR), and ecological suitability (soil type, rainfall, and location altitude). The results show that socially, the community accepts and has even implemented the concept of multi-business forestry through agroforestry. However, most permit holders consider it necessary to regulate the number of trees to optimize land use. Economically, all multi-business patterns implemented are feasible, with the presence of aren (Arenga pinnata) and sheep being important keys to the sustainability of SF. Ecologically, some NTFPs species cultivated by the community are less suited to local conditions, which can result in suboptimal production. The existence of investors or business entities is very important in the sustainability of forestry multi-businesses, which are mostly based on NTFPs and require high capital.